Some Practical Methods for the Application of 5-Metallo-1-benzyl-1H-tetrazoles in Synthesis - Wiedemann, Sean H.; Bio, Matthew M.; Brown, Liane M.; Hansen, Karl B.; Langille, Neil F. (Synlett, 2012)
Nucleophilic reagents such as 5-lithiotetrazoles are synthetically powerful tools for the installation of tetrazole functional groups, but they are of limited utility due to the instability of tetrazole-derived carbanions. Herein, we report practical methods for the generation and use of new 5-metallo-1-benzyl-1H-tetrazoles (M = K, MgX, ZnX) derived from either 1-benzyl-1H-tetrazole or 1-benzyl-5-bromo-1H-tetrazole. By varying the metal counterion, the tetrazole carbanion stability was improved. Potassium- and magnesium-derived reagents underwent additions to carbonyl compounds at –30 and –20 °C, respectively. The isolated yields (41–85%) from these and other reactions were comparable to those reported for 5-lithiotetrazoles at much lower temperatures (–78 to –98 °C).
Keywords: nucleophilic addition; Grignard reaction; metalation; tetrazoles; counterion effects